A holistic provenance and microwear study of pre-colonial jade objects from the Virgin Islands: Unravelling mobility networks in the wider Caribbean. (February 2022) - Knaf, Alice C.S.; Falci, Catarina Guzzo; Habiba; Toftgaard, Casper J.; Koornneef, Janne M.; van Gijn, Annelou; Brandes, Ulrik; Hofman, Corinne L.; Davies, Gareth R.
Highlights: Novel application of a minimally invasive portable laser ablation sampling device with subsequent low-blank geochemical analyses. A trace element and multi-isotopic analysis of pre-colonial jade artefacts recovered from the Virgin Islands. Typo-technological and microwear study of jade artefacts from Ceramic Age settlements on St. Croix. Predictive modelling of artefact provenance based on trace elements by applying a binary logistic regression method. Artefacts from Ceramic Age sites on St. Croix, St. Thomas and St. John include Guatemalan, Cuban and Dominican material. Evidence of large scale (>3000 km) pre-colonial mobility networks in the Greater Caribbean. Abstract: Pre-colonial Caribbean jade objects from the National Museum of Denmark Hatt Collection were subjected to a provenance and microwear analysis. Thirty-nine jade celts and bodily ornaments from the US Virgin Islands, i.e., St. Croix, St. Thomas, St. John, and five celts from the West Indies of unknown location, St. Vincent, Cuba and the Dominican Republic were analysed. A comprehensive in-depth examination of jade adornments from St. Croix, combining typo-technological and microwear analysis, is compared to other lithologies used for pre-colonial ornaments. A portable laser ablation system was used to sample jade celts and bodily ornaments on site in a quasi-non-destructive manner. Low-blank trace element and Sr-Nd isotope ratio data were evaluated with a multiclass regression provenance prediction model. This study demonstrates that the pan-Caribbean exchange of jade raw materials, pre-forms or finished objects during the Ceramic Age (400 BC to AD 1492) occurred on a more complex scale than previously thought involving jade sources in Guatemala, eastern Cuba and the northern Dominican Republic. In addition, the study of ornaments recovered from St. Croix reveals use of specific lithologies suggesting stronger ties to Indigenous communities on Puerto Rico than other Lesser Antillean Islands.